A Syntactical Analysis of Sentences Written by Deaf Students at the Senior High Level of a Public Special School in Sumbawa Regency - Haerani, Aditiya; Jazadi, Iwan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The purpose of this study was to determine the syntactic ability and the form of syntactic errors at the writing of deaf students at the senior high school level of Public Special School (SLBN) 1 Sumbawa. Participants in this study were five students consisting of 1 of the10th grade, 3 of the 11th students, and 1 of the 12th grade. The research was qualitative, while the data were collected using written tests. For the data analysis, the researchers used the theory of Chaer about syntactic functions and devices. The results of the study show that the forms of errors in the student's writing consist of errors on the use of subjects, predicates, objects, and adverbs. Other forms of errors lie in the order of words, word forms, and use of conjunction. Another finding is that some students were able to compile sentences based on S + Adv + P, while the other students were only able to compile sentences with the S + Adj pattern. Based on these findings, it is expected that parents or teachers play a role to teach children or students how to compose sentences with a simple pattern so that children who suffer from deafness are able to convey what they want to convey.